Calibration of whole body counter for assessment of internal dose in the human body. Issue 1 (January 2021) - Dararutana, C; Abdullah, N
Abstract: In the Malaysian Nuclear Agency (Nuklear Malaysia), the ORTEC Whole Body Counter System, bed type was used for assessing internal dose due to intake of gamma radionuclides in the human body. In this study, the performance of ORTEC Whole Body Counter System includes energy calibration, counting efficiency, validation test and minimum detectable activity (MDA) for the radionuclides of interest (ROI) has been investigated using ORTEC whole body counter phantom and mixed standard sources having gamma energies between 59.5 keV and 1836.2 keV. Later, the whole body counting was performed to determine the existence of any gamma radionuclides in the body. The result of the energy calibration was within the tolerance limit of ± 5%. The counting efficiency varies between 0.0000881 cps/Bq and 0.000332 cps/Bq. The results of the validation test show that the bias (Br ) and repeatability (SBr ) are within the acceptable range of -0.25 ≤ Br ≤ +0.50 and SBr ≤ 0.40, respectively. The MDA for each ROI of I-131, Cs-137 and Co-60 were 165.4 ± 10.0 Bq, 144.6 ± 11.5 Bq and 167.3 ± 30.5 Bq, respectively. A total of 14 volunteers from Postgraduate Educational Course in Radiation Protection and Safety of Radioactive Sources (PGEC-16) were invited to perform the whole body counting. Each volunteer was scanned for 1200 s with the bed speed of 0.065 inch/s. The results show that there is no internal exposure found for all monitored person. Consequently, it can be concluded that the ORTEC Whole Body Counter System (WBC) is now ready to be used for internal dose assessment.